The Influence of Human Resources and Work Environment on the Performance Of Employees In The Directorate Of Samapta, Metro Jaya Regional Police - Arif Prasetyo; Yuni Pratikno; Sitta Kusuma (Dinasti International Journal of Digital Business Management, 2026)
This study aims to determine and analyze the influence of human resources on employee performance, the influence of the work environment on employee performance, and the influence of human resources and the work environment simultaneously on employee performance at the Samapta Directorate of the Jakarta Metropolitan Police. This research is important to conduct considering that the Samapta Directorate has a strategic role in carrying out police operational tasks that require personnel readiness, professionalism, and support for a conducive work environment. The quality of human resources that include competence, motivation, and work experience, as well as a safe, comfortable, and collaborative work environment, is believed to contribute directly to employee performance achievements. The type of research used is quantitative research with an associative approach, namely to examine the relationship and influence between variables objectively through numerical data processing. However, this study is also supplemented with qualitative data as supporting data, such as the results of observations, limited interviews, and respondents' statements in questionnaires, in order to obtain a more comprehensive understanding of actual conditions in the field. The population of this study amounted to 89 personnel of the Samapta Directorate of the Jakarta Metropolitan Police, and the entire population was used as respondents so that the sampling technique used was a census. Hypothesis testing was conducted using SPSS version 27 software. The results of the study indicate that partially human resources (X₁) and work environment (X₂) have a positive and significant effect on employee performance (Y). Simultaneously, both independent variables are also proven to have a significant effect on employee performance. The coefficient of determination (R-Square) value of 0.309 or 30.9% indicates that employee performance can be explained by human resources and work environment, while the remaining 69.1% is influenced by other factors outside this study, thus opening opportunities for further research to examine additional variables